SOX2 mediates cisplatin resistance in small‐cell lung cancer with downregulated expression of hsa‐miR‐340‐5p - Fei Cui; Zhe‐xue Hao; Jin Li; Ya‐lei Zhang; Xu‐kai Li; Jian‐xing He (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background This study is aimed to unravel the genetic factors associated with microRNA (miRNA) expression in regulating sex‐determining region Y‐box 2 (SOX2)‐mediated cisplatin resistance in small‐cell lung cancer (SCLC). Methods The relevance of SOX2 expression in SCLC was analyzed in a panel of SCLC cells by quantitative real‐time PCR (qPCR) and western blot (WB). We selected DMS114 cell line, in which SOX2 was amplified via lentiviral vector‐mediated transfection of the SOX2 genes and tested for the half‐maximal inhibitory concentration (IC50) by MTS assay. High‐throughput sequencing and screening of differentially expressed miRNAs between SOX2‐overexpressing and normal control cells were performed. Finally, miRanda software was used to verify the miRNAs bound with SOX2 and qPCR was used to identify the expression of miRNAs which were binding with SOX2. Results Cisplatin‐resistant SOX2‐overexpressing DMS114 cell lines were successfully developed, showing a statistically significant increase in SOX2 expression by qPCR and WB. Our results showed a typically higher IC50 value in SOX2‐overexpressing cells compared with the negative controls. The high‐throughput sequencing analysis revealed that 68 miRNAs were upregulated and 24 miRNAs were downregulated in the SOX2‐overexpressing cells. The 24 downregulated miRNAs were further verified. Of them, a cancer‐related miRNA, hsa‐miR‐340‐5p, showed a higher binding affinity with SOX2 in network regulation mapping, which was also found to be markedly downregulated under qPCR analysis. Conclusion We demonstrated that downregulated expression of hsa‐miR‐340‐5p may affect cisplatin resistance by mediating SOX2 expression in SCLC cells, which may provide a potential target for the therapy of chemoresistant SCLCs.